Quando uma garota entra em um bar: uma análise do consumo feminino de cerveja em um ambiente historicamente masculinizado - Klock, Douglas Araujo (Universidade do Vale do Rio dos Sinos, 2018)
In general, consumer studies place women under three different prisms: as a coadjuvant, when considering that their consumption activities depend on the masculine, seeking conditions of equity when analyzing when it masculiniza to a situation of consumption or in conservative positions, by studying consumption in their roles as mother, wife or in household-related processes. Aligned with Pierre Bourdieu who advocates the existence of a kind of male domination in society, operating through well defined mechanisms and their reflexes can be seen in consumer behavior. Specifically, beer and bar in Brazil are reflections of this pre-established dynamics, where the woman is seen as an object within a historically masculinized environment. The objective of this dissertation is to analyze the female consumption of beer in bars in the city of Porto Alegre and to verify the possible influence of socio-historical consumer patterns, describing the female behavior within the studied context. For this, a qualitative research was carried out, inspired by ethnographic studies, at the moment of the consumption of beer by women in bars of the city, identifying the meanings and the representations of the female consumption of beer. The results were structured in three parts for discussion: first through market mythologies that interfere with consumption. In the second part through the discourses and the reflex in the feminine behavior. The third part brings the context and the product through the lens of the interviewees. This study encouraged theoretical contributions in advancing the position of women in consumer studies in a privileged position within a masculinized environment, suggesting the existence of unfoldments for new studies. From a professional point of view, the study inspires a set of practical suggestions to make female beer consumption experiences more inclusive using brand positioning, market performance of companies in the sector and the emergence of new products.
Keywords: Pierre Bourdieu; Consumo e gênero; Cerveja e o bar; Consumer culture theory; Pierre Bourdieu; Consumption and gender; Beer and the bar; Consumer culture theory; ACCNPQ::Ciências Sociais Aplicadas::Administração